A critical review in recent progress of hollow fiber membrane contactors for efficient CO2 separations. (June 2023) - Imtiaz, Aniqa; Othman, Mohd Hafiz Dzarfan; Jilani, Asim; Khan, Imran Ullah; Kamaludin, Roziana; Ayub, Muhammad; Samuel, Ojo; Kurniawan, Tonni Agustiono; Hashim, NurAwanis; Puteh, Mohd Hafiz
Abstract: Among wide range of membrane-based operations, membrane contactors, as they reify comparatively modern membrane-based mechanism are gaining quite an attention in both pilot and industrial scales. In recent literature, carbon capture is one of the most researched applications of membrane contactors. Membrane contactors have the potential to minimize the energy consumption and capital cost of traditional CO2 absorptions columns. In a membrane contactor, CO2 regeneration can take place below the solvent boiling point, resulting into lower consumption of energy. Various polymeric as well as ceramic membrane materials have been employed in gas liquid membrane contactors along with several solvents including amino acids, ammonia, amines etc. This review article provides detailed introduction of membrane contactors in terms of CO2 removal. It also discusses that the main challenge that is faced by membrane contactors is membrane pore wetting caused by solvent that in turn can reduce the mass transfer coefficient. Other potential challenges such as selection of suitable solvent and membrane pair as well as fouling are also discussed in this review and are followed by potential ways to reduce them. Furthermore, both membrane gas separation and membrane contactor technologies are analysed and compared in this study on the basis of their characteristics, CO2 separation performances and techno economical transvaluation. Consequently, this review provides an opportunity to thoroughly understand the working principle of membrane contactors along its comparison with membrane-based gas separation technology. It also provides a clear understanding of latest innovations in membrane contactor module designs as well as challenges encountered by membrane contactors along with possible solutions to overcome these challenges. Finally, semi commercial and commercial implementation of membrane contactors has been highlighted. Graphical abstract: Image 1 Highlights: Comprehensive review of membrane contactors for CO2 separation. Review for conventional membrane gas separation technology and membrane contactors. Latest innovations in membrane contactor module designs. Challenges encountered by membrane contactors for CO2 separation.